Cover Image. (15th August 2018) - Weck, Philippe F.; Gordon, Margaret E.; Greathouse, Jeffery A.; Bryan, Charles R.; Meserole, Stephen P.; Rodriguez, Mark A.; Payne, Clay; Kim, Eunja
Abstract : The cover image, by Philippe F. Weck et al., is based on the Research Article Infrared and Raman spectroscopy of α‐ZrW2 O8 : A comprehensive density functional perturbation theory and experimental study, https://doi.org/10.1002/jrs.5396 .